Oxford urdu ka guldasta Sada bahar grade 3 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Oxford Urdu Ka Guldasta Sada Bahar (Grade 3)" is a collection of engaging Urdu stories, poems, and rhymes designed for third-grade students. The book offers a variety of content that helps children improve their Urdu language skills, including vocabulary, reading comprehension, and sentence structure. With colorful illustrations and captivating narratives, it not only makes learning Urdu fun but also imparts important moral lessons. The stories and poems are tailored to be age-appropriate, fostering an appreciation for the Urdu language while encouraging young readers to develop their reading and language abilities.
Keywords: Urdu : Textbook